A case of paraplegia due to limb girdle muscular dystrophy with coexisting gitelman’s syndrome - Manappallil, Robin George (Asian Journal of Medical Sciences, 2016)
Muscular dystrophies are a rare group of disorders affecting the skeletal muscles, which are progressive, hereditary and degenerative. A sudden worsening of the condition should raise the possibility of hypokalemia, followed by its evaluation and correction. The patient being reported is a 33 year old lady who presented with generalized but mainly bilateral lower limb proximal muscle weakness; and was diagnosed to have limb girdle muscular dystrophy (LGMD), with the support of muscle biopsy and electromyography (EMG) study. However, her laboratory investigations showed hypokalemia, hypomagnesemia and hypocalciuria, suggestive of an underlying Gitelman’s syndrome (GS). Such a scenario has rarely been reported. Asian Journal of Medical Sciences Vol.7(5) 2016 129-131